Rasio N-NO3-:P dan Pengaturan Kepekatan Larutan Nutrisi Untuk Pembungaan Waluh Berbasis Hidroponik Substrat - Ariwati Trisiwi Marhaeni; Endang Setia Muliawati; Retna Bandriyati Arniputri (Agrotechnology Research Journal, 2018)
Pumpkin is a promising commodity to be developed as food substitute for flour-based flour. Pumpkin cultivation is currently cultivated by farmers on dry land as secondary crop. Pumpkin cultivation constraints as requires a large area and long time. Pumpkin commodities development can be done by hydroponic substrates cultivation that have advantages to accelerate the plant growth, can be cultivated on limited area, and increase the quality of plant yields. The hydroponic substrate cultivation depends on the quality of nutrients as well as the availability of the nutrients. The aim of this research is to study the response of plant flowering to the composition of nutrients (modification of the balance of Nitrogen and Phosphor) and concentration of hydroponic substrate nutrition solution and interaction between treatments. This research used Completely Randomized Design which consists of 2 factors, nutritional composition and concentration of solution with 3 replications and each treatment consist of 6 plants. Observation variables included flower age, flower position, and number of flowers. The results showed that there were interactions between the treatment of nutrient composition and adjustment concentration on the observing variables flower age appear, and flower position. Nutritional composition with the balance of elements of Phosphorus and Nitrogen shows the higher balance of Phosphorus elements followed by lower Nitrogen elements tend to give a lower response to flowering pumpkin on hydroponic substrate. Adjustment lower concentration of application solutions (20 ml concentrated in 1 L solution) or equivalent to EC 3.8-4.0 mS/cm gives a better response to flowering pumpkin on hydroponic substrate.